Defensa de la vida: more-than-human care as resistance against the threats of mega-projects at the Isthmus of Tehuantepec, Mexico - Philipp, Rosa (Geoforum, 2025)
This paper examines practices of resistance to the Interoceanic Corridor mega-project in southern Mexico, focusing on how women1 are defending their lives in the face of violence from the extractive mega-infrastructure project’s impact on their territories and bodies. The mega-infrastructure project’s objective is to unite the Atlantic and Pacific Oceans at the Isthmus of Tehuantepec. By promoting regional development and modern progress, the Interoceanic Corridor has engendered discontent and instigated protests among the Indigenous and local communities. These resistance movements at the Isthmus of Tehuantepec are part of broader national and international initiatives aimed at safeguarding territorio (territory) threatened by neoliberal development and mega-projects. Engaging with feminist decolonial epistemology, this paper investigates the notion of defensa de la vida (defence of life) and explores how life itself becomes a form of resistance, manifesting through care for human and more-than-human beings. Based on ethnographic fieldwork between 2021 and 2023, including interviews, observations and workshops with women from the Isthmus of Tehuantepec, this paper illustrates how women defend their territorio and lives. This resistance is embodied in their embrace of community, their reciprocal care for more-than-human beings and their daily practices, rituals and celebrations. By tracing these multiple practices of care as mundane forms of everyday resistance, this paper broadens the conception of resistance through care by including a more-than-human dimension.